Graft utilization after normothermic regional perfusion in controlled donation after circulatory death—a single‐center perspective from France. (26th August 2021) - Muller, Xavier; Rossignol, Guillaume; Damotte, Sophie; Gregoire, Arnaud; Matillon, Xavier; Morelon, Emmanuel; Badet, Lionel; Mohkam, Kayvan; Lesurtel, Mickaël; Mabrut, Jean‐Yves
Summary: Normothermic regional perfusion (NRP) in controlled donation after circulatory death (cDCD) is a promising procurement strategy. However, a detailed analysis of graft utilization rates is lacking. This retrospective study included all cDCD donors proposed to a single center for NRP procurement of at least one abdominal organ from 2015 to 2020. Utilization rates were defined as the proportion of transplanted grafts from proposed donors in which withdrawal of life sustaining therapies (WLST) was initiated. In total, 125 cDCD donors underwent WLST with transplantation of at least one graft from 109 (87%) donors. In a total of 14 (11%) procedures NRP failure led to graft discard. Utilization rates for kidney and liver grafts were 83% and 59%, respectively. In 44% of the discarded livers, the reason was poor graft quality based on functional donor warm ischemia >45 min, macroscopic aspect, high‐transaminases release, or pathological biopsy. In this study, abdominal NRP in cDCD lead to transplantation of at least one graft in the majority of cases. While the utilization rate for kidneys was high, nearly half of the liver grafts were discarded. Cannulation training, novel graft viability markers, and ex‐vivo liver graft perfusion may allow to increase graft utilization. Abstract : In this study, normothermic regional perfusion in controlled donation after circulatory death lead to transplantation of at least one graft in the majority of donors. However, while the utilization rate for kidneys was high, nearly half of the liver grafts were discarded.